Marriage by capture - Barnes, R (Royal Anthropological Institute of Great Britain and Ireland, 1999)
The theories of John F. McLennan have long been dismissed as disproved or passe. Meanwhile, modern ethnography has produced increasingly sophisticated ethnographic accounts relevant to his ideas. This article looks at a sample of that ethnography from Indonesia, the Caribbean, Amazonia, Australia and New Guinea to see what it might have to say about McLennan's hypotheses, particularly in respect to marriage by capture and linguistic exogamy. Modern anthropological discussions are reminiscent in many ways of McLennan's, perhaps unconsciously so. McLennan would probably be quite pleased to have access to the information now available and undoubtedly would attempt to exploit it to defend his views. In the end, the new information does not support his theories, but we may still lack final answers to his questions.